Strategi Guru Akidah Akhlak dalam Menanggulangi Kenakalan Siswa Pasca Daring di MTs Negeri 3 Agam - Sari, Fitri Nila; Aprison, Wedra (TSAQOFAH, 2023)
The method used in this study is qualitative that researchers will see or observe natural objects. The research approach used is a qualitative description of a method that describes what happened in the field of akidah teacher's strategy for containing post-online student delinquency in MTSN 3 religions. The data gathering technique by observing school and class environment then interviewing akidah teacher and a few Indonesian students and teachers. The typical prank of MTSN 3 is that students often enter the classroom late, and boys don't follow the dress code and students often say bad things to their teachers and friends. How the whole world of akidah teachers take over this post-online delinquency. And what are the factors against and supporting akidah teacher's strategy to combat post-online student delinquency in MTSN 3 religion. From research, akidah teacher's strategy for overcoming delinquent students who are late into the classroom is with preventive measures that are being given taulans, reciting prayers. The law repressive action of repeating prayer in front of the class aloud, of standing in front of the class while raising his hand for a few minutes. A strategy for overcoming male students who do not follow the dress code is given a repressive measure by reproving errors and punishing by overturning the shirt.A teacher's strategy against delinquency that speaks impolitely by giving preventive measures of addressing students with the importance of modesty, the repressive act of reprimanding them for their errors, being directed at forgiveness, punishing by instructing to learn the scriptures or the hadith. Inhibitors come from a school environment, poor teacher cooperation, influence of peers, lack of parent cooperation and teachers keep a record of problem students' names. Support factors from school and parental support.